Analisis Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai BKPSDMD Kabupaten Batang Hari - Niki Kosasih; Maya Hartanti (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
To improve employee performance, a human resource management strategy is needed in order to improve the performance of BKPSDMD employees in Batang Hari Regency. This study aims to determine: 1) To find out the strategy of managing human resources at the Regional Personnel and Human Resources Development Agency (BKPSDMD) Batang Hari Regency, 2) To determine the performance of employees at the Regional Personnel and Human Resources Development Agency ( BKPSDMD) Batang Hari Regency. The type of research used is descriptive qualitative, with data collection techniques of observation, interviews, documentation and literature study. The results show that the benefits of the human resource management strategy implemented by the Regional Personnel and Human Resources Development Agency (BKPSDMD) of Batang Hari Regency can directly provide good results in improving the performance of the Regional Personnel and Human Resources Development Agency (BKPSDMD) of Batang Hari Regency.